Desafios à formação educacional de surdos no Brasil e a proposta de educação bilíngue - ROMEIRO, Adrielle da Silva Santos (2020)
Accordingto IBGE estimates, amongthe 207 millionBrazilianinhabitants, 5.1% are hearingimpairedand1 million are youngerthan 19 yearsold. Butofthese 1 millionyoungstersanddeafchildren, howmanyhavehadtheopportunitynotonlyto go toschoolbutalsotohaveaneducational background thatrespectstheirspecificities?Thisstudyseekstoidentifywhicheducationalfactorsh avemadetheeducational background ofdeafpeople in Braziltobechallenging in regular schoolsthatadopttheproposalof inclusive education. In ordertohighlightthesechallenges, I make theoretical approaches onthehistoryofdeafeducation, as well as therightofpeoplewithspecialneedstoeducation, bringingto light the reality ofthedeafstudent in thepracticeof inclusive education. Basedonthese approaches, I bringanaccountofexperiencethat I experiencedatan inclusive school in Belém, where I hadtheopportunityto observe thedailylivesofthreedeafstudents in thepracticeof inclusive education.The studiesthroughthisworkevidencethatwhenreceiving a deafstudent, theschoolneedsto assume anenvironmentthatensuresrespect for thelinguisticdifferencesofthisstudent, for this, neednotonlyspecializedteachers, orthepresenceofaninterpreter in theclassroom, but it isnecessaryto assume theimportanceofworkingtoacquirethelanguageofthedeafstudent in signlanguage: LIBRAS, respecting it as thenativelanguageofthedeaf, and for this, theparticipationofbilingualteachers, deafandofthedeafcommunity. Andfromthis perspective, schoolsthat assume a philosophyofbilingualeducationdemonstratethemselves as a betteralternativetoguaranteethisspace.